VALIDITAS INSTRUMEN PENILAIAN KEMAMPUAN BERPIKIR KRITIS PADA MATERI SISTEM PERNAPASAN - Kurniawati, Ananda Ayu; Sabtiawan, Wahyu Budi (Program Studi S1 Pendidikan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2023)
The purpose of this research is to make an evaluation tool for critical thinking skills related to the subject matter of the respiratory system. This study used a research and development approach using the Planning, Production, and Evaluation (PPE) framework. The research process consists of three fundamental stages, namely the planning stage, the production stage, and the evaluation stage. The assessment instrument has gone through a validation process involving three validators. Assessment of the validity of the material consists of five aspects that must be examined, one of which is related to the suitability of the questions with indicators of critical thinking. The material validity assessment shows a validity value of 100% which indicates the ability of the instrument to measure the material in question accurately. The assessment of the construction aspect consists of eight aspects that must be reviewed resulting in a validity value exceeding 75% for each item indicating that the developed instrument meets the validity criteria. The assessment of the language aspect which consists of five aspects that must be studied produces a validity value that exceeds 75% for each item so that it shows the validity of this instrument. This shows that the evaluation tool in the form of an assessment instrument for critical thinking skills that has been developed can be declared valid for evaluating critical thinking skills in the material on the respiratory system.